„Jak ghetto – ty ublížíš mně, já ublížím tobě.“: Bezpečnost a pouliční násilí v sociálně vyloučené lokalitě - Walach, Václav; Císař, Ondřej (Lidé města, 2024)
This paper empirically examines the meaning of security within a socially excluded locality. Drawing on critical security studies and cultural criminology, ethnographic research was conducted to make sense of security from the perspective of the excluded. We provide an account of the dominant security narrative identified in the investigated discourse, where street violence is recognized as the most serious threat to the well-being of a local population. Violence is understood both as a means of satisfying drug addiction and as a mechanism of creating ’respect’. The interpretation is further analyzed through a framework inspired by the thought of Pierre Bourdieu, utilizing the concepts of street culture field, street capital, and street habitus. In the conclusion of the article, we claim that street violence is not the manifestation of the Roma ethnicity, as some put it, but that it should be approached as a symptom of social marginalization instead.